Bone turnover alterations across the menopausal transition in south-eastern Chinese women. (3rd July 2016) - Ma, L.; Song, Y.; Li, C.; Wang, E.; Zheng, D.; Qu, F.; Zhou, J.
Abstract: Objectives: To explore the serum levels of bone resorption marker C-terminal telopeptide of type I collagen (CTX) and bone formation marker N-amino terminal propeptide of type I collagen (PINP) in Chinese women across the menopausal transition and the correlation between follicle stimulating hormone (FSH), luteinizing hormone (LH) and estradiol with the bone turnover markers. Methods: A cross-sectional study was conducted on 464 healthy Chinese women, separated into pre-, peri- and postmenopausal groups based on their menstruation changes. The serum levels of CTX, PINP, FSH, LH, and estradiol were measured. Results: The serum levels of CTX and PINP were significantly higher in women in the peri- and postmenopausal groups. The serum levels of FSH were significantly correlated with the serum levels of PINP in premenopausal women. Both serum FSH and LH were positively correlated with serum CTX in perimenopausal women and postmenopausal women. Estradiol was inversely correlated with CTX in the perimenopausal group. Multiple linear regression models show the serum FSH levels were independently related to the bone turnover markers CTX and PINP. Conclusions: The elevated serum levels of FSH were independent risk factors for bone loss in peri- and postmenopausal women, and measurement of the serum FSH levels in mid-age women with irregular menses could be used in early diagnosis of postmenopausal osteoporosis.